PERSEPSI MASYARAKAT PASIR TUMBOH TERHADAP MADRASAH DINIAH BAKRIAH PONDOK PASIR TUMBOH KOTA BHARU KELANTAN MALAYSIA DALAM PEMBELAJARAN KITAB HADIS BULUGHUL MARAM - Nur Amirah Syuhada Binti Supia Sughari (UIN Sumatera Utara Medan, 2020)
The research focuses on the perception of the community in Pasir Tumboh towards Madrasah Diniah Bakriah Pondok Pasir Tumboh Kota Bharu Kelantan, Malaysia in the study of Hadith using the book entitled Bulugh Al-Maram. The findings suggest that the community in Pasir Tumboh are very interested in studying the course. However, the theory and practice are not correlated with each other since the community are still lacking in understanding the hadith book thoroughly